Geographically structured genetic variation in Ptychozoon lionotum (Squamata: Gekkonidae) and a new species from an isolated volcano in Myanmar - Grismer, L. Lee; Wood, Perry L. Jr.; Thura, Myint Kyaw; Grismer, Marta S.; Brown, Rafe M.; Stuart, Bryan L. (Zootaxa, 2018)
A molecular phylogenetic analysis of Parachute Geckos (Genus Ptychozoon Kuhl & van Hasselt, 1822) based on the mitochondrial gene ND2 indicates that a newly discovered population from the Mt. Popa volcano—a habitat island in the northern portion of the Bago Yoma mountains, Myanmar—is a new species, P. popaense sp. nov. This species is part of a clade that contains P. bannanense Wang, Wang, & Liu, 2016 and P. lionotum Annandale, 1905 of Indochina. Ptychozoon popaense sp. nov. is morphologically most similar to its sister species P. lionotum which manifests considerable geographic substructuring of genetic variation but differs from the nominate taxon by an uncorrected pairwise sequence divergence of 16.0–17.1% and by discrete differences in morphology and color pattern. This discovery highlights the unique, insular nature of the Bago Yoma mountains of the Ayeyarwady Basin, which support other endemic gekkonids. It also underscores the growing diversity in this highly derived clade of cryptic, parachuting, geckos characterized by highly divergent genetic lineages, which may indicate the presence of additional, unrecognized species.